2023
DOI: 10.3389/fendo.2023.1166953
|View full text |Cite
|
Sign up to set email alerts
|

AVP deficiency (central diabetes insipidus) following immunization with anti-COVID-19 BNT162b2 Comirnaty vaccine in adolescents: A case report

Abstract: IntroductionThe coronavirus disease 19 (COVID-19) pandemic has prompted the development of new vaccines to reduce the morbidity and mortality associated with this disease. Recognition and report of potential adverse effects of these novel vaccines (especially the urgent and life-threatening ones) is therefore essential.Case presentationA 16-year-old boy presented to the Paediatric Emergency Department with polyuria, polydipsia and weight loss over the last four months. His past medical history was unremarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There is no description of the recovery of hormone levels in the three previous cases of hypopituitarism induced by COVID-19 vaccines [ 11 13 ]. In some cases of AVP deficiency, long-term replacement of vasopressin is necessary [ 6 8 , 11 ]. Nevertheless, it is also reported that in about half cases of thyroid disorder, at least partial recovery was observed within 5 months [ 11 ], indicating a relatively better prognosis in ASIA than other etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no description of the recovery of hormone levels in the three previous cases of hypopituitarism induced by COVID-19 vaccines [ 11 13 ]. In some cases of AVP deficiency, long-term replacement of vasopressin is necessary [ 6 8 , 11 ]. Nevertheless, it is also reported that in about half cases of thyroid disorder, at least partial recovery was observed within 5 months [ 11 ], indicating a relatively better prognosis in ASIA than other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…These vaccines can cause various side effects such as pain, swelling, fever, headache, and diarrhea [2]. Regarding the pituitary gland, pituitary apoplexy [3][4][5] and arginine vasopressin (AVP) deficiency [6][7][8][9][10][11] have rarely been reported after COVID-19 vaccination. Only three cases of hypophysitis and anterior pituitary hormone deficiency have been reported: low insulin-like growth factor [11], isolated adrenocorticotropic hormone (ACTH) deficiency [12], and anterior hypopituitarism [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pituitary disorders were initially reported in the setting of SARS-CoV2 infection, followed by published clinical cases of hypophysitis, central diabetes insipidus, SIADH, pituitary apoplexy, and ACTH deficiency as rare adverse effects of the vaccination. The summarized cases of pituitary conditions are not very numerous, but perhaps the actual incidence is underreported and thus underestimated [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104]. In addition, a delay in diagnosis can arise from overlapping symptoms related to pituitary hormone deficiencies and those experienced after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning hypophysitis, this is a sporadic disease with an incidence of ~1 in 9 million/year in the form of primary hypophysitis [96]. Hypophysitis following SARS-CoV-2 vaccine present most often as isolated arginine vasopressin (AVP) deficiency (central diabetes insipidus) due to infundibuloneurohypophysitis [89,[97][98][99]. AVP deficiency was also reported with subsequent development of optic neuritis [100].…”
Section: Pituitary Gland and Sars-cov-2 Vaccinementioning
confidence: 99%
“…Several types of COVID-19 vaccines, such as mRNA, adenoviral vectors and inactivated vaccines, have been marketed in various countries to reduce infection and mortality rates. It is not clear whether there is an increased risk of endocrine disease morbidity after vaccination, but some endocrine diseases were reported after vaccination, such as type 1 diabetes mellitus, 4 thyroiditis, 5 Graves’ disease, 6 AVP deficiency (central urolithiasis), 7 optic neuritis and pituitary inflammation comorbidities, 8 , 9 and even adrenal crisis secondary to COVID-19 vaccination in patients with hypopituitarism. 10 In this paper, we report a case of hypophysitis after COVID-19 vaccination in a patient with Rathke’s cleft cyst to raise attention to the rare but serious adverse reactions for early recognition and intervention.…”
Section: Introductionmentioning
confidence: 99%